A Case of Primary Hypoparathyroidism Presenting with Acute Kidney Injury Secondary to Rhabdomyolysis. (10th March 2016) - Sumnu, Abdullah; Aydin, Zeki; Gursu, Meltem; Uzun, Sami; Karadag, Serhat; Cebeci, Egemen; Ozturk, Savas; Kazancioglu, Rumeyza
Abstract : Hypoparathyroidism is the most common cause of symmetric calcification of the basal ganglia. Herein, a case of primary hypoparathyroidism with severe tetany, rhabdomyolysis, and acute kidney injury is presented. A 26-year-old male was admitted to the emergency clinic with leg pain and cramps, nausea, vomiting, and decreased amount of urine. He had been treated for epilepsy for the last 10 years. He was admitted to the emergency department for leg pain, cramping in the hands and legs, and agitation multiple times within the last six months. He was prescribed antidepressant and antipsychotic medications. He had a blood pressure of 150/90 mmHg, diffuse abdominal tenderness, and abdominal muscle rigidity on physical examination. Pathological laboratory findings were as follows: creatinine, 7.5 mg/dL, calcium, 3.7 mg/dL, alanine transaminase, 4349 U/L, aspartate transaminase, 5237 U/L, creatine phosphokinase, 262.000 U/L, and parathyroid hormone, 0 pg/mL. There were bilateral symmetrical calcifications in basal ganglia and the cerebellum on computerized tomography. He was diagnosed as primary hypoparathyroidism and acute kidney injury secondary to severe rhabdomyolysis. Brain calcifications, although rare, should be considered in dealing with patients with neurological symptoms, symmetrical cranial calcifications, and calcium metabolism abnormalities.